2010
DOI: 10.2298/sos1003337w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering time on the microstructure and properties of inorganic polyphosphate bioceramics

Abstract: Sintering is an important step in the fabrication process of ceramic bodies, which can significantly affect the microstructure and properties of materials. In this article, calcium based inorganic polyphosphate (CPP) bioceramics were synthesized by gravity sintering. Effects of the sintering time (30 minutes, 1 hour, 3 hours and 5 hours) on the microstructure, physicochemical degradation and mechanical property were investigated. It was found that all prepared CPP samples for various sintering times show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
10
1
2
Order By: Relevance
“…The porosities of CCPP scaffolds measured by liquid displacement method were shown in Table 3 which were similar to the results of the literature. 21 The compressive strength of CCPP scaffold with the porosity of 70% was 5-9 MPa which met the strength requirements of cancellous bone (2-12 MPa). It indicated that this CCPP scaffold could serve as a promising candidate for bone repairing.…”
Section: Resultsmentioning
confidence: 80%
“…The porosities of CCPP scaffolds measured by liquid displacement method were shown in Table 3 which were similar to the results of the literature. 21 The compressive strength of CCPP scaffold with the porosity of 70% was 5-9 MPa which met the strength requirements of cancellous bone (2-12 MPa). It indicated that this CCPP scaffold could serve as a promising candidate for bone repairing.…”
Section: Resultsmentioning
confidence: 80%
“…Principally, absorption of FTIR band before and after compression showed similar features. That morphology of drug components can be analyzed using SEM [22][23]. SEM is an analysis technique used to observe the changes in particle morphology caused by compression pressure, including sintering phenomena.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…The volume of pores in the sample was obtained from the diference in the initial and inal (after 2 h) displacement readings of ethanol in the tube. The porosity of the sample was then calculated from the ratio of pores and total volume [33,34].…”
Section: Porosity and Density Analysismentioning
confidence: 99%